2021
DOI: 10.1515/bejeap-2020-0319
|View full text |Cite
|
Sign up to set email alerts
|

The Gender Wage Gap among Ph.D. Holders: Evidence from Italy

Abstract: This paper contributes to the literature on the gender wage gap by empirically analyzing those workers who hold the highest possible educational qualification, i.e., a Ph.D. The analysis relies on recent Italian cross-sectional data collected through a survey on the employment conditions of Ph.D. holders. The Oaxaca–Blinder decomposition analysis and quantile decomposition analysis are carried out, and the selection of Ph.D. holders into employment and STEM/non-STEM fields of specialization is taken into accou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 84 publications
3
7
0
Order By: Relevance
“…Moreover, they are less likely to be satisfied with their job. Confirming past evidence (Alfano, Cicatiello, et al, 2019; Croce & Ghignoni, 2015), we find significant gender discrimination, with females having less favourable job opportunities than males. Unexpectedly, being Married and having Children do not play a role.…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…Moreover, they are less likely to be satisfied with their job. Confirming past evidence (Alfano, Cicatiello, et al, 2019; Croce & Ghignoni, 2015), we find significant gender discrimination, with females having less favourable job opportunities than males. Unexpectedly, being Married and having Children do not play a role.…”
Section: Resultssupporting
confidence: 90%
“…To be coherent with the European classification, the 14 fields are aggregated into three groups (Science and medicine; Physics and engineering; Social sciences), which are also those on which calls for research projects in all European countries are focussed. For these reasons and in line with previous studies (i.e., Alfano, Cicatiello, et al, 2019;Alfano, D'Uva, et al, 2019;Gaeta, 2015;Parenti et al, 2020), we adopt the European classification. However, we also ran the regressions with the 14 categories, and the main results were unchanged.…”
Section: Resultsmentioning
confidence: 91%
“…These results are similar to those found in another recent analysis that focused on PhD holders. For example, the rates of this unexplained gap are in line with the findings of Schulze (2015) for the UK academic sector and Alfano et al (2021) for Italy. In the case of South Korea, Park (2018), who employed Heckman's two‐step approach to correct for sample selection bias, detected an unexplained wage gap of 41.9 per cent among PhD holders.…”
Section: Analysis Resultssupporting
confidence: 87%
“…Previous studies on PhD holders have emphasised the glass ceiling (Schulze 2015; Alfano et al 2021), but this study is the first to analyse the distributional patterns of the gender gap with homogeneous PhD holders in South Korea, confirming both limited glass ceilings and obvious sticky floors. Although a number of previous studies have suggested that higher education mitigates gender discrimination, our analysis challenges this view (Piazzalunga 2018).…”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation